Penggandaan Kromosom dan Pertumbuhan Somaklonal Andalas (Morus macroura Miq. var macroura) yang Diperlakukan dengan Kolkisin - Anzharni Fajrina; M Idris; - Mansyurdin; Netty W Surya (Jurnal Biologi Universitas Andalas, 2012)
The aim of this research was to find the best concentration of colchicine and soaking time to induce tetraploid plants and to study the growth responses of Andalas somaclone. The colchicine concentrations consist of 0.05, 0.1; 0.15% with soaking time were 72 and 96 hours respectively. The results showed that the concentration of 0.05% colchicine with 96 hours soaking time able to induce highest percentage shoot of Andalas tetraploid (75%). The highest percentage of roots induction and the best timing of root formation were obtained at concentration of 0.05% colchicine with 96 hours soaking time.Keywords: Morus macroura Miq. var macroura,somaclone, growth, chromosomes, colchicine